Lo schermo, la tela, la finestra (e altre superfici quadrangolari normalmente verticali) - Mauro Carbone (Rivista di Estetica, 2014)
Though the image of vision still dominant is that of the window, my hypothesis is that the optical apparatus we implicitly refer to nowadays has become the screen, which shows many differences from the window. Therefore I believe that to understand how we conceive our present experience of screens, it would be helpful to comprehend our present experience of seeing. I think also that our present screens experience is the result of the screens experience that cinema taught us, even if many differences separate nowadays those two experiences. On this subject, we know that the opaque surface of the screen has traditionally been considered to hamper vision and therefore to conceal truth. On the contrary, the advent of cinema has shown how the opacity of such a surface can actually make us see, thus reminding us that light and shade – traditionally opposed by our culture – simply cannot be separated. But this is not enough: it shall be added that such a surface has always solicited and oriented the desire of he or she who contemplated it. If such a desire used to coincide with the possibility of seeing beyond the screen, today the screen surface rather envelops us in a reversible visibility, inviting us to dwell in it. We may then connect the century of cinema – that has just ended – to a progressive affirmation of a different way of conceiving the giving of our encounter with the world. Such a way shall slip from a theatrical apparatus like that of the window (that is, par excellence, a representative apparatus opening up through the opening of a curtain) to a cinematographic apparatus, of which I try to outline a few characteristics in my essay.